Exploring the contribution of formal and informal learning to academic staff member employability: A Dutch perspective. Issue 3 (3rd June 2014) - Van der Klink, Marcel; I.J.M. Van der Heijden, Beatrice; Boon, Jo; Williams van Rooij, Shahron
Abstract : Purpose: – Little attention has been paid to the employability of academic staff and the extent to which continuous learning contributes to academic career success. The purpose of this paper is to explore the contribution of formal and informal learning to employability. Design/methodology/approach: – Survey data were obtained from 139 academic staff members employed at the Open University in the Netherlands. The questionnaire included employee characteristics, job characteristics, organizational context factors, formal learning and informal learning and employability variables. Findings: – Informal learning, such as networking and learning value of the job, appeared to be solid contributors to employability, while the impact of formal learning activities was far less significant. Further, the study revealed the impact of employee and organizational context factors upon informal learning and employability. Age, salary and learning climate appeared to be strong predictors for informal learning, while promotions were shown to be highly positive contributors to employability. Practical implications: – The findings stress the value of informal learning, although human resource policies that encourage both formal and informal learning are recommended. Originality/value: – Academic careers comprise an under-researched area and the same applies to the relationship between learning and employability in the context of these types of careers.